2014
DOI: 10.1136/bcr-2013-200718
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculous mediastinal lymphadenopathy in an adult

Abstract: We describe a patient who presented to us with fever, decreased appetite, weight loss and dry cough for 1 month with no abnormalities on examination. A chest radiograph showed a mediastinal shadow. CT of the chest revealed multiple mediastinal lymph nodes. Bronchoalveolar lavage was negative for acid-fast bacilli and cytological examination did not show malignant cells. Serum ACE levels were high (93 U/L). Bone marrow aspiration and biopsy did not reveal any pathology. Mediastinoscopy-guided mediastinal lymph … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…In Patients of our cohort, isolate mediastinal lymphadenopathy was detected in 46% of non-necrotizing granulomatous inflammation. ; this rate was 25% in patients diagnosed with tuberculosis (7,8). In our study, in both groups 1 and 2 the most common secondary pathologies were hilar LAP and parenchymal nodules (Figs.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In Patients of our cohort, isolate mediastinal lymphadenopathy was detected in 46% of non-necrotizing granulomatous inflammation. ; this rate was 25% in patients diagnosed with tuberculosis (7,8). In our study, in both groups 1 and 2 the most common secondary pathologies were hilar LAP and parenchymal nodules (Figs.…”
Section: Discussionsupporting
confidence: 52%
“…The easiest and quickest method of diagnosis is ARB via the Ehrlich-Ziehl-Nielsen staining method. However, to show bacteria with direct microscopy, the material must contain at least 5000 to 10000 bacteria per mL [8]. In a study of newly diagnosed tuberculosis patients, it was reported that smear positivity could be shown in 50% to 80% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Isolated mediastinal lymphadenopathy is not unusual in children but rarely described in adults in the absence of associated parenchymal lesions. 1 Mediastinal lymph nodes can be enlarged in various pathological conditions like TB, sarcoidosis, lymphoma, and metastatic lung cancer. 2 A sampling of mediastinal lymph nodes is paramount for diagnosing these conditions and for staging patients with bronchogenic carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence rates of tuberculous mediastinal lymphadenitis are 5% to 17.6% of total TB cases and decreased with the increasing of age. [ 14 , 15 ] Although, it is usually asymptomatic, the symptoms was reported that lymph nodes compresses upon adjacent structures. [ 4 ] The sensitivity of CT scanning on tuberculous lymphadenitis is 57% in total.…”
Section: Discussionmentioning
confidence: 99%